Parenting Patterns in Teach-Free Parenting and Early Childhood Social Development: Pola Asuh dalam Teach-Free Parenting dan Perkembangan Sosial Anak Usia Dini - Nisa, Kholifatun; Habibah, Sulhatul; Fauziyah, Nina Rohmatul (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Early childhood represents a critical developmental phase in which social competencies such as empathy, cooperation, and communication begin to form through interactions within family and educational environments. Specific Background: In the digital era, millennial parents increasingly adopt teach free parenting, a flexible and communicative approach that allows children to learn through direct experience with guided boundaries. Knowledge Gap: Despite its growing relevance, empirical understanding of how millennial parents implement teach free parenting and its role in early childhood social development remains limited, particularly in Indonesian early childhood education contexts. Aims: This study aims to describe parenting patterns of millennial parents in applying teach free parenting and examine its role in shaping social development among kindergarten children in Lamongan. Results: Using a qualitative case study with in-depth interviews involving parents and teachers, findings indicate that teach free parenting reflects a balance between child autonomy and parental guidance, fostering confidence, empathy, cooperation, and communication skills through open dialogue, decision-making opportunities, and consistent support. Challenges include environmental influences, gadget use, and differing family parenting patterns, while parent–school collaboration emerges as a key supporting factor. Novelty: The study highlights teach free parenting as an adaptive transformation of democratic parenting within the digital era, emphasizing experiential learning and guided autonomy. Implications: These findings provide practical insights for parents and educators to implement adaptive parenting strategies that support consistent social value internalization and collaborative educational environments. Highlights• Flexible caregiving approach balances autonomy with structured guidance• Social competencies emerge through dialogue and experiential learning• Parent–school synergy supports consistent developmental processes KeywordsTeach Free Parenting; Millennial Parents; Early Childhood; Social Development; Democratic Parenting